Unexpected Genomic and Phenotypic Diversity of Mycobacterium africanum Lineage 5 Affects Drug Resistance, Protein Secretion, and Immunogenicity. (13th July 2018) - Ates, Louis S; Dippenaar, Anzaan; Sayes, Fadel; Pawlik, Alexandre; Bouchier, Christiane; Ma, Laurence; Warren, Robin M; Sougakoff, Wladimir; Majlessi, Laleh; van Heijst, Jeroen W J; Brossier, Florence; Brosch, Roland
Abstract: Mycobacterium africanum consists of Lineages L5 and L6 of the Mycobacterium tuberculosis complex (MTBC) and causes human tuberculosis in specific regions of Western Africa, but is generally not transmitted in other parts of the world. Since M. africanum is evolutionarily closely placed between the globally dispersed Mycobacterium tuberculosis and animal-adapted MTBC-members, these lineages provide valuable insight into M. tuberculosis evolution. Here, we have collected 15 M. africanum L5 strains isolated in France over 4 decades. Illumina sequencing and phylogenomic analysis revealed a previously underappreciated diversity within L5, which consists of distinct sublineages. L5 strains caused relatively high levels of extrapulmonary tuberculosis and included multi- and extensively drug-resistant isolates, especially in the newly defined sublineage L5.2. The specific L5 sublineages also exhibit distinct phenotypic characteristics related to in vitro growth, protein secretion and in vivo immunogenicity. In particular, we identified a PE_PGRS and PPE-MPTR secretion defect specific for sublineage L5.2, which was independent of PPE38. Furthermore, L5 isolates were able to efficiently secrete and induce immune responses against ESX-1 substrates contrary to previous predictions. These phenotypes of Type VII protein secretion and immunogenicity provide valuable information to better link genome sequences to phenotypic traits and thereby understand the evolution of the MTBC.